Comprehensive Evaluation of the Postharvest Antioxidant Capacity of Majiayou Pomelo Harvested at Different Maturities Based on PCA - Zhengpeng Nie; Chunpeng Wan; Chuying Chen; Jinyin Chen (MDPI AG, 2019)
Majiayou pomelo (Citrus grandis L. Osbeck, MP) is a famous local red pulp pomelo from the Jiangxi province in China that is rich in natural active substances. In order to investigate the postharvest antioxidant capacities of MP pulp and determine the optimal harvesting time, fruits that were harvested at three different maturities (185, 200, and 215 days after full bloom) were observed for 180 days of preservation at ambient temperature. An abundance of ascorbic acid and lycopene in the MP pulp was found during storage, and in Harvest I, these substances were significantly higher than in Harvest II and Harvest III fruit (p < 0.05). The activity of ascorbate peroxidase (APX), peroxidase (POD), and catalases (CAT) in Harvest I and Harvest II were far higher after 90 days. The radical scavenging ability of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, superoxide anion radical (O2−•), and hydroxyl radical (•OH) in Harvest I and Harvest II were higher. There was a significantly positive correlation (p < 0.01) between the antioxidant components (ascorbic acid, lycopene, carotenoids, total phenols, and total flavonoids), enzyme activity, and radical scavenging ability. The comprehensive scores determined by principal component analysis (PCA) in Harvest I and II were higher than those in Harvest III. Therefore, the optimal harvesting period of MP for each year is determined to be early November. The study provides a theoretical basis for the maintenance of the postharvest fruit value and the regulation of fruit functional components.